Lee Myung Bak’s Choice on Sunshine Policy: South Korean National Interests and North Korean Threat - Darynaufal Mulyaman (Sospol : Jurnal Sosial Politik, 2018)
Sunshine Policy that had been implemented by South Korean Government on Kim Dae-Jung and Roh Moo-Hyeon’s administration from 1998-2008. This policy started to do cooperative behavior for treating North Korea as a partner, not contrarily, yet the Sunshine Policy was considered as a failure by Lee Myung-Bak’s administration, thereupon stopped offhandedly despite recent cultural and cooperative diplomacy that had been done by his successor President Moon Jae-In. Then Why the South Korean government at the time of President Lee Myung-Bak stopped the Sunshine Policy offhand? In the scheme of National Interest idea, North Korea still a predominant threat that very paramount for South Korean national interest, even an accommodative and cooperative policy like Sunshine Policy could not emphasize South Korean national interests. This paper also tries to analyze the issue with explaining foreign policy decision making factors, such as the domestic and external factor, decision environment, and psychology factor of President Lee Myung-Bak at that time.